Closed-loop design of fault detection for networked non-linear systems with mixed delays and packet losses - Feng, Jian; Wang, Shenquan; Zhao, Qing (IET control theory & applications, 2013)
This study is concerned with the problem of fault detection (FD) for networked control systems with discrete and infinite distributed delays subject to random packet losses and non-linear perturbation. Both sensor-to-controller and controller-to-actuator packet losses are modelled as two different mutually independent Bernoulli distributed white sequences with known conditional probability distributions. By utilising an observer-based fault detection filter (FDF) as a residual generator, the FD for networked non-linear systems with mixed delays and packet losses is formulated as an H∞ model-matching problem. Attention is focused on designing the FDF in the closed-loop system setup such that the estimation error between the residuals and filtered faults is made as small as possible and at the same time the closed-loop networked non-linear system is exponentially stable in the mean-square sense. To show the superiority and effectiveness of this work, two numerical examples are presented.